Myofibroblast‐dominant proliferation associated with severe fibrosis in bulbar urethral strictures. (20th September 2022) - Hirano, Yusuke; Horiguchi, Akio; Ojima, Kenichiro; Azuma, Ryuichi; Shinchi, Masayuki; Ito, Kenichi; Miyai, Kosuke
Abstract : Objectives: Myofibroblast‐dominant proliferation (relative to fibroblast proliferation) is the key process in urethral fibrosis, but its association with clinical features is not understood. We conducted a histological analysis of urethral strictures and examined the association between myofibroblast proliferation and stricture characteristics. Methods: Formalin‐fixed, paraffin‐embedded urethral sections sliced axially from 175 male patients with bulbar urethral strictures were retrospectively analyzed. All patients underwent excision and primary anastomosis between September 2008 and January 2021 by a surgeon (AH). Masson's trichrome stain was used to estimate the area of fibrosis. Corresponding unstained slides with the largest area of fibrosis were selected and double‐immunostained with anti‐smooth muscle actin (SMA) and anti‐TE‐7 mouse monoclonal antibodies for the assessment of myofibroblasts and fibroblasts, respectively. The ratio of the number of SMA‐positive cells to the number of TE‐7‐positive cells (SMA/TE‐7 ratio) was calculated. Results: The area of fibrosis in strictures due to perineal trauma ( n  = 85, median 108.9 mm 2 ) was significantly larger than that in non‐traumatic strictures ( n  = 90, median 42.9 mm 2, p  < 0.0001). The area of fibrosis positively correlated with SMA expression ( r  = 0.35, p  < 0.0001) and the SMA/TE‐7 ratio ( r  = 0.36, p  < 0.0001), but not with TE‐7 expression (r = −0.01, p  = 0.75). In a multivariate linear regression model, traumatic etiology (standard coefficient 0.37, t value 3.9, p  < 0.0001) and increased SMA expression (standard coefficient 0.17, t value 2.1, p  = 0.03) were the predictors of wide fibrosis area. Conclusions: Myofibroblast‐dominant proliferation may contribute to the pathogenesis of severe urethral fibrosis.